Treatment of pubic symphysis infection with vancomycin-loaded calcium sulfate artificial bone combined with debridement in pediatric patients: a case report and literature review - De-zhi, Su; Gang-quan, Wu; Shi-min, Ye; Kun, Wang; Ying-chou, Lu; Guo-min, Zhai; Zhe-min, Zhu; Yi, Yang; Bao-biao, Zhuo (Frontiers in Surgery, 2025)
ObjectiveTo investigate the clinical characteristics of pubic symphysis infection and evaluate the safety and efficacy of vancomycin-loaded calcium sulfate (VCS) artificial bone combined with debridement in treating these infections in adolescents.MethodsWe retrospectively analyzed a clinical case and supplemented our findings with a narrative literature review. The evaluation focused on a 13-year-old female patient diagnosed and treated at our hospital in February 2025. To contextualize our case, we searched PubMed, Wanfang, China National Knowledge Infrastructure (CNKI), VIP, and China Biology Medicine (CBM) databases for articles available from the establishment of each database up to April 2023. Data from the present case and previously documented cases of pubic symphysis infection in pediatric patients who met the inclusion criteria were compiled. The data, with a particular focus on clinical presentations, treatment modalities, and follow-up outcomes, were analyzed to draw comparative insights regarding treatment efficacy.ResultsA comprehensive literature review identified eight documented pediatric cases of pubic symphysis infection, each presented as individual case reports. Notably, one of these cases lacked identifiable risk factors. All patients were effectively managed through conventional surgical débridement in conjunction with antibiotic therapy. In the current case, the patient underwent a two-stage intervention that included the implantation of vancomycin-loaded calcium sulfate (VCS) beads, débridement of the pubic symphysis, and bilateral pubic fenestration and drainage. This was succeeded by a six-week regimen of postoperative antibiotic therapy. The patient exhibited an excellent recovery, characterized by normalized bilateral hip range of motion and absence of tenderness over the pubic symphysis. Follow-up imaging revealed the resorption of the VCS beads and bilateral callus formation. Unlike previously reported cases, the treatment strategy implemented in this instance obviated the necessity for repeated débridement and dressing changes, thereby significantly reducing patient discomfort.ConclusionThe application of VCS combined with debridement was effective in controlling infection and promoting bone regeneration in this pediatric case, offering a promising therapeutic approach for similar rare infections.